Digital Transformation and Human Resource Competence As Drivers of Operational Effectiveness: The Mediating Role of Organizational Innovation in Port Operations - Robert Edward; Putri Wulandari Sinar Bulan (MASI Mandiri Edukasi, 2026)
Organizations operating in operational-intensive environments, such as port services, face increasing pressure to enhance operational effectiveness amid rapid digital disruption. Although digital transformation initiatives have been widely implemented, many organizations struggle to translate technological adoption into tangible operational improvements. This study aims to examine the effects of digital transformation and human resource (HR) competence on operational effectiveness, with organizational innovation positioned as a mediating variable. This research applies a quantitative explanatory design using a causal approach. Data were collected through structured questionnaires distributed to 200 respondents, consisting of 100 internal employees and 100 external port service users at PT Pelindo (Persero) Regional 2, Sunda Kelapa Branch. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software to evaluate the measurement and structural models and test the proposed hypotheses. The findings reveal that digital transformation has a positive and significant effect on organizational innovation, and that HR competence also significantly influences it. Furthermore, organizational innovation has a strong positive effect on operational effectiveness and partially mediates the relationship between digital transformation and HR competence. These results indicate that technological initiatives and human resource capabilities contribute more effectively to operational performance when supported by strong organizational innovation mechanisms.